Exergy as a means for process integration in an integrated steel plant - Elfgren, Erik; Grip, Carl-Erik; Wang, Chuan; Karlsson, Jonny (Luleå tekniska universitet, Energivetenskap, 2011)
The Luleå energy system consists of SSAB (an integrated steel plant) – LuleKraft (the heat and power plant) – Luleå Energi (the district heating network). The exergy flows in the whole system have been studied and some possibilities on how to reduce the exergy losses are discussed. The exergy thermal efficiency of SSAB, LuleKraft and Luleå Energi are 70 %, 40 % and 30 % respectively. The relatively low exergy thermal efficiencies is a natural consequence of converting high-value chemical energy into heating water. In the integrated steel plant, the exergy losses are caused by the cooling of the steel prior to transport. In the heat and power plant, exergy is destroyed mainly in the furnace. In the district heating, exergy is destroyed mainly by the customer. A preliminary conclusion is that a lot of exergy is destroyed and lost in order to produce hot water, which doesn’t really need so much exergy. By lowering the water temperature of the district heating, a larger portion of the exergy can be converted to high-value electricity. Mapping by combined Exergy/energy analysis is important to find ways to improve energy efficiency. It can also be important to initiate regional energy collaboration. Godkänd; 2011; 20110920 (ysko)